El tratamiento de las unidades fraseológicas en el diccionario de Franciosini (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
The aim of this essay is to focus on some aspects about the presence of idioms in Franciosini’s Italian-Spanish dictionary, published in 1620; we will take into consideration the issue from a diachronical and contrastive perspective, and we will underline those features which reappear in the actual dictionaries too.
Keywords: phraseology, translation, lexicography, diachrony, contrastive lexicography